Infectious Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Virus in Symptomatic Coronavirus Disease 2019 (COVID-19) Outpatients: Host, Disease, and Viral Correlates. (23rd November 2021) - Mollan, Katie R; Eron, Joseph J; Krajewski, Taylor J; Painter, Wendy; Duke, Elizabeth R; Morse, Caryn G; Goecker, Erin A; Premkumar, Lakshmanane; Wolfe, Cameron R; Szewczyk, Laura J; Alabanza, Paul L; Loftis, Amy James; et al.
Abstract: Background: Although severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infectious virus isolation in outpatients with coronavirus disease 2019 (COVID-19) has been associated with viral RNA levels and symptom duration, little is known about the host, disease, and viral determinants of infectious virus detection. Methods: COVID-19 adult outpatients were enrolled within 7 days of symptom onset. Clinical symptoms were recorded via patient diary. Nasopharyngeal swabs were collected to quantitate SARS-CoV-2 RNA by reverse transcriptase polymerase chain reaction and for infectious virus isolation in Vero E6-cells. SARS-CoV-2 antibodies were measured in serum using a validated ELISA assay. Results: Among 204 participants with mild-to-moderate symptomatic COVID-19, the median nasopharyngeal viral RNA was 6.5 (interquartile range [IQR] 4.7–7.6 log10 copies/mL), and 26% had detectable SARS-CoV-2 antibodies (immunoglobulin (Ig)A, IgM, IgG, and/or total Ig) at baseline. Infectious virus was recovered in 7% of participants with SARS-CoV-2 antibodies compared to 58% of participants without antibodies (prevalence ratio [PR] = 0.12, 95% confidence interval [CI]: .04, .36; P  = .00016). Infectious virus isolation was also associated with higher levels of viral RNA (mean RNA difference +2.6 log10, 95% CI: 2.2, 3.0; P  < .0001) and fewer days since symptom onset (PR = 0.79, 95% CI: .71, .88 per day; P  < .0001). Conclusions: The presence of SARS-CoV-2 antibodies is strongly associated with clearance of infectious virus. Seropositivity and viral RNA levels are likely more reliable markers of infectious virus clearance than subjective measure of COVID-19 symptom duration. Virus-targeted treatment and prevention strategies should be administered as early as possible and ideally before seroconversion. Clinical Trials Registration: NCT04405570. Abstract : Among COVID-19 outpatients within 7 days of symptom onset, the presence of SARS-CoV-2-specific antibodies was strongly associated with clearance of infectious virus. Seropositivity appears to be more reliable marker of infectious virus clearance than patient-reported COVID-19 symptoms.